LITERATURE REVIEW STUDY ON EFFICIENCY AND EFFECTIVENESS OF FINANCIAL MODELLING FOR INVESTMENT DECISIONS OF INDIVIDUAL INVESTORS - Gupta, Shubhangi; Lande, Ganesh Sambhaji (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In today’s volatile and information-driven financial environment, individual investors are increasingly seeking tools that enhance the quality and reliability of their investment decisions. Financial modelling, once primarily used by institutional investors and analysts, is now gradually making its way into personal finance due to the rise of user-friendly digital platforms and fintech applications. This study investigates the efficiency and effectiveness of financial modelling tools in empowering individual investors to make informed, data-driven, and goal-oriented investment decisions. The research explores key dimensions such as the level of awareness, usage patterns, perceived effectiveness, and the actual benefits derived from financial modelling tools among retail investors. It also delves into the various barriers that hinder the widespread adoption of such tools, including lack of financial literacy, complexity in usage, and mistrust of algorithm-based advice. Data was collected through structured questionnaires and analyzed using descriptive statistics and hypothesis testing to assess correlations between investor behavior and tool usage. The findings reveal a clear positive correlation between financial literacy and effective use of modelling tools, with users reporting improved decision confidence, risk assessment, and goal planning. The study also highlights the need for simplified interfaces, personalized insights, and educational interventions to bridge the gap between potential and actual usage. By identifying critical gaps and actionable insights, this research contributes to the broader conversation on democratizing investment intelligence and equipping individual investors with strategic tools to navigate complex markets effectively.